Недоторканність права власності та заходи забезпечення кримінального провадження (частина 1) - Крикунов, О.; Krykunov, A. (Волин. нац. ун-т ім. Лесі Українки, 2018)
Досліджено передбачені чинним кримінальним процесуальним законодавством форми обмеження права власності. Встановлено підстави для тимчасового доступу до речей та документів та їх виїмки, тимчасового вилучення майна, а також підстави для повернення майна їх законним володільцям. Визначено об’єкти права власності, які може бути вилучено згідно із КПК України під час названих заходів забезпечення кримінального провадження. З’ясовано гарантії належного зберігання вилученого майна. За підсумками дослідження сформульовано пропозиції по удосконаленню чинного КПК України. The study highlights the forms of limitation of the right upon ownership imposed by the current criminal procedure law. The author considers the grounds for granting a court's permission for temporary access to things and documents and their seizure, imposition of seizure on the property, temporary seizure of property and the grounds for the return of property to their legitimate owners. The study analyzes the guarantees of proper storage of seized property. The author offers a supplement the сriminal-зrocedural norms regarding the non-return of the temporarily withdrawn property, when, in accordance with the civil law, it can not be owned by the citizens, public associations, international organizations and legal entities of other states on the territory of Ukraine or when the person has no special permission for a certain kind of property. The author argues the necessity of foreseeing the possibility of an appeal against the decisions of the investigating judge to satisfy the complaint of the legitimate owner regarding the non-return of the temporarily seized property by the investigator or the prosecutor.
Krykunov A. Inviolability of Property Right and Measures of Ensuring of Criminal Proceedings (Part 1)
Keywords: право власності; тимчасовий доступ до речей; документів та їх виїмка; тимчасове вилучення майна; арешт майна; кримінальне провадження; property right; temporary access to things; documents and their seizure; temporary seizure of property; arrest of property; criminal proceedings